Collaborative natural resource governance for biodiversity and livelihoods around protected areas : a dual case study of Kaingu and Kaindu, Zambia - Luaba, Kampinda (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.